Distance Education Tutors’ Acceptance Of Learning Management System For Blended Learning In Ghana - Bervell, Brandford (2018)
This study proposed a conceptual framework based on the Unified Theory of Acceptance and Use of Technology (UTAUT) and Social Cognitive Theory of Information System (SCT-IS) to investigate tutors’ acceptance of Learning Management System (LMS)-enabled blended learning in distance education (DE). Anchored on embedded mixed method (Quantitative + qualitative) design, the questionnaire and interview guide were utilized for data collection. Consequently, quantitative data was drawn from a sample of 267 tutors from DE study centres across Ghana who responded to the questionnaire, while 15 of them were interviewed for the qualitative component. Analysis of the quantitative data utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique while thematic analysis was used for the qualitative data. Findings from the research revealed key factors of tutors’ LMS-enabled blended learning uptake intention as attitude, self-efficacy, previous technology experience and effort expectancy. However, the Importance Performance Map Analysis (IPMA) results proved that attitude towards LMS-enabled blended learning was the most important and performing factor shapening the intentions of tutors towards blended learning acceptance in DE. Furthermore, the study established non-linear relationships among both personality factors (attitude, self-efficacy, previous technology experience and anxiety) and UTAUT exogeneous factors (performance expectancy, effort expectancy, social influence and facilitating conditions) towards behavioural intention.